A Comparative Model of Mysticism: Cognitive Neuroscience, Phenomenal Experiences, and Noetic Accounts - Trivedi, Hemal P. (Archive for the psychology of religion, 2025)
This article proposes a model of comparative mysticism that bases its rationale for comparison in the dynamic interaction between three components: neurocognitive mechanisms and substrates, phenomenal experiences, and noetic accounts. In examining the phenomenon of ego-dissolution (EDn), using this model, a scholar can identify universal and contextual components of a mystic’s experiences. The neurocognitive component is derived from neuroscientific studies including brain injury, psychedelics, and meditative practices. The phenomenal and noetic components are derived from personal accounts as narrated by the mystics themselves. These three components will be applied to the ego-dissolution experiences of the modern Indian mystic Sadhguru (1957–Present), the medieval Spanish mystic Teresa of Ávila (1515–1583), and individuals, including scientists, using the psychedelics psilocybin and LSD. This model should introduce an alternative approach to comparative mysticism as a response to the long-standing debate between Walter T. Stace’s essentialist model and Steven T. Katz’s contextualist model, respectively. In particular, the neurocognitive component should function as a bridge providing a deeper level of analysis encompassing and undermining differences between universalist and contextualist reductions. The advent of comparative mysticism may be seen as a collaborative effort that is multidisciplinary in nature, contributing to theology, religious studies, philosophy, history, cognitive neuroscience, and many other disciplines.